Survey on School Awareness in Protecting Students' Personal Data at Vocational High Schools in Manado using ISO 27001:2022 Framework - Diana Khuntari; Arum Marwati; Rahmat Rian Hidayat; Nopriadi; Sigit Permasnyah (Jurusan Teknik Informatika dan Komputer, 2025)
In the digital era, personal data protection has become a crucial concern, especially in educational institutions. This study aims to evaluate the level of school awareness in protecting students' personal data at vocational high schools in Manado, Indonesia. A quantitative survey method was employed, involving 111 respondents consisting of Principal, teachers, IT staff and students from five vocational high schools. Data were collected using a structured questionnaire based on the ISO 27001:2022 standard, which covers four control domains: organizational, human, physical, and technological. The instrument's validity and reliability were confirmed through content validation and Cronbach's Alpha analysis. The results indicate that SMKs in Manado demonstrate a relatively high level of awareness across all domains, particularly in technological and organizational controls. However, gaps remain in the implementation of formal policies and consistent practices. This study highlights the novelty of applying ISO 27001:2022 as an assessment framework for educational institutions in Indonesia, which is rarely explored in existing literature. The findings suggest the need for continuous training and structured policy development to ensure sustainable data protection practices. These results can serve as a foundation for policymakers and school administrators to enhance data security readiness in the education sector.